(3aj GdQVGYs - (3GdYHGj GdgTJQhOj GdJHQjRj, aQL Gddg Hf eMeO, J (B1339 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3eSFdI UQM LeGYI ef GdCUMGH HCf MdjdI GdGHf GdQVGYj JMQe Ydi GdCH GdQVGYj ceG JMQe GdGe GdQVGYj ddRhLI Ydi GdRhL hGOYi aj GdLhgQ YOe GdNdGa ajg (B...s
(3BNQgG (B:s
... (3hGdeSJfO aj gPg hChLg GMJeGd GdYdGbI (B... (3aj ehVY ef GdbhGYO YOe JSHjH GdQVGY dKHhJ GdJMQje HGdeUGgQI (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B3 - 95 ( 615)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis